Differences between carbon suboxide and its heavier congeners as ligands in transition metal complexes: a theoretical study. (7th October 2016) - Zhang, Zhong; Pu, Liang; Zhao, Xiao; Li, Qian-shu; King, R. Bruce
Abstract : The lowest energy structures for the [M](C3 E2 ) complexes ([M] = Ir, Ni, Pt surrounded by ligands such as phosphines and halides; E = O, S, Se) are compared. Abstract : A density functional theory study of experimentally reported [M](C3 E2 ) complexes ([M] = Ir, Ni, Pt surrounded by ligands such as phosphines and halides; E = O, S, Se) suggests that the behaviors of C3 O2 and C3 E2 (E = S, Se) as ligands in transition metal complexes differ significantly. The lowest energy structures for the [M](C3 O2 ) complexes have the C3 O2 ligand bonded to the transition metal through a CC double bond. However, the lowest energy structures for the [M](C3 E2 ) (E = S, Se) complexes have the C3 E2 ligand bonded to the transition metal through a CE double bond. The latter structures are confirmed by comparison of the experimental infrared frequencies arising from the C3 E2 ligand with our theoretical results.